Provenance and transport mechanism of marine sediments in the Zhongjiannan Basin - Wu, Xuewan; Shi, Chaoqi; Guo, Feng; Li, Zihan; Luo, Junsheng; Li, Peipeng; Wang, Ziwen; Wang, Guifeng; Wan, Zhifeng (Frontiers in Marine Science, 2024)
The research on the source of marine sediments has a vital impact on identifying material sources, transport mechanism, and the evolution of sedimentary environments. Previous studies have shown many outstanding achievements on the source analysis of the South China Sea, but there are still some controversies over the complex source and transport mechanisms of the Zhongjiannan Basin. In this study, we took a gravity core (583cm) from the Zhongjiannan Basin and analyzed the particle size, rare earth elements, and Sr-Nd isotopes of the core sediments to further reveal the source and transport mechanism. The surface sediments in the Zhongjiannan Basin were relatively stable, with an average particle size ranging from 5.66 to 17.74 μm. The normalized standard curve of chondrite exhibited the depletion of Eu, with LREE dominated in REE. As the depth increased, 87Sr/86Sr ratios showed a gradually increasing trend, while δNd change was relatively complex. On the whole, 87Sr/86Sr ratios (from 0.721537 to 0.725322) and δNd (from -11.561617 to -12.289374) were in a relatively narrow range. Based on the particle size characteristics, we found the geochemical characteristics of sediment largely resulted from different sediment sources. By comparing rare earth elements and Sr-Nd isotopes, we concluded the sediment of the Zhongjiannan Basin was from mainly terrigenous contribution. In addition, taking into account factors such as terrain, migration distance, and river drainage system, we conclude the sediment were mainly from the Mekong River, the Red River, Taiwan Island, and Hainan Island. The surface current along the northeast direction was the main transportation route for the sediments of the Mekong River. The Guangdong coastal current and the southwest surface current transported sediment from the Red River and Hainan Island to the Zhongjiannan Basin. The surface current and deep-water current in the southwest direction carried sediment from Taiwan Island to the study area, while the Kuroshio also had some impacts on the sediment transportation of Taiwan Island. This study has reinforced the research on provenance in the South China Sea Basin and has an important significance on evolution of sedimentary environments, evolution of ancient oceans.